1998
DOI: 10.1007/s002130050705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isolation-rearing on locomotion, anxiety and responses to ethanol in Fawn Hooded and Wistar rats

Abstract: Voluntary ethanol (EtOH) consumption is increased by isolation-rearing in several rat strains. The following experiments examined the effects of isolation-rearing on basal and ethanol-stimulated behavior in Fawn Hooded rats, an alcohol-preferring rat strain, compared to Wistar rats. Locomotor activity and anxiety were examined under both conditions. Basal locomotor activity was higher in isolated subjects of both strains in low light conditions, but under bright light conditions, this difference was only obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
54
1
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 38 publications
11
54
1
4
Order By: Relevance
“…On the contrary, our data show that isolation rearing does not affect on motor impulsivity and only affects cognitive impulsivity when rats are intoxicated (Hellemans et al, 2005). Although contrary to our hypothesis, these data are consistent with evidence that isolation rearing enhances behavioural responses to ethanol (Hall, Huang, Fong, Pert, & Linnoila, 1998a) and does not effect impulsivity in an attentional task, except under the influence of amphetamine (Dalley, Theobald, Pereira, Li, & Robbins, 2002b). These findings led us to conclude that the relationship between adverse early experience and impulsivity is mediated by an intervening variable such as stress, which may be induced by drug administration.…”
Section: The Study Of Individual Differencessupporting
confidence: 80%
“…On the contrary, our data show that isolation rearing does not affect on motor impulsivity and only affects cognitive impulsivity when rats are intoxicated (Hellemans et al, 2005). Although contrary to our hypothesis, these data are consistent with evidence that isolation rearing enhances behavioural responses to ethanol (Hall, Huang, Fong, Pert, & Linnoila, 1998a) and does not effect impulsivity in an attentional task, except under the influence of amphetamine (Dalley, Theobald, Pereira, Li, & Robbins, 2002b). These findings led us to conclude that the relationship between adverse early experience and impulsivity is mediated by an intervening variable such as stress, which may be induced by drug administration.…”
Section: The Study Of Individual Differencessupporting
confidence: 80%
“…The anxiolytic effects of ethanol have been extensively described (Bilkei-Gorzo et al, 1998;Colombo et al, 1995;Ferreira et al, 2000;Gallate et al, 2003;Hall et al, 1998;Martijena et al, 2001;Martin-Garcia and Pallares, 2005;Varlinskaya and Spear, 2002). In fact, although a previous study indicated that adolescent rats may be less sensitive than adults to the anxiolytic effects of ethanol (Varlinskaya and Spear, 2002), a recent study (Hefner and Holmes, 2007) showed that adolescent C57BL/6J mice exhibit increased sensitivity to anxiolytic-like effects of ethanol when compared to adults.…”
Section: Anxiolytic Effects During Adolescent Exposurementioning
confidence: 99%
“…Excessive alcohol consumption by anxious patients, presumably due to the anxiolytic properties of alcohol, has led to the hypothesis that anxiety could be a critical factor in the etiology of alcohol drinking (Colombo et al, 1995). The anxiolytic-like effects of ethanol associated with forced and acute administration (Bilkei-Gorzo et al, 1998;Ferreira et al, 2000;Hall et al, 1998;Martijena et al, 2001;Varlinskaya and Spear, 2002) or voluntary ethanol consumption (Colombo et al, 1995;Gallate et al, 2003) have been extensively described in different rodent tests. In addition, in contrast to the effect described during exposure, the occurrence of an anxiogenic-like effect during ethanol withdrawal has been reported (Kliethermes, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Birds reared by parents of another species fail to develop species-typical calls (Immelmann, 1969). In rats, variations in rearing environment ranging from normative differences in maternal licking and grooming to more extreme interventions such as social isolation are associated with altered stress responsiveness and changes in social behavior in adulthood (Hall et al, 1998;Liu et al, 2000). Human infants raised in socially deprived environments show decreased social interaction as children, exhibiting some of the features of autism (Rutter et al, 1999).…”
Section: Introductionmentioning
confidence: 99%